Retrospective study of patients on hybrid dialysis: Single-center data from North America. Issue 2 (March 2020) - Sriperumbuduri, Sriram; Biyani, Mohan; Brown, Pierre Antoine; McCormick, Brendan B
Hybrid dialysis involves combining peritoneal and hemodialysis (HD) in patients with end-stage renal disease. Its reported use is quite limited outside of Japan. We present a retrospective review of 18 patients at our center that received this therapy and describe their ultimate disposition. We observed that 39% of the population on hybrid dialysis ultimately transitioned to full in center HD, 28% continue until death, and 33% either transition to home HD or received a transplant. In our center, hybrid dialysis was successful as a bridging therapy or in balancing continuation of dialysis with quality of life among those with a limited prognosis.